How Can Regional Collaborative Governance Promote Public Value Through Relational Leadership? Grounded Research Based on Inter-Provincial Collaboration Between Guangdong, Hunan, and Guangxi in China - Feng, Bo; Xing, Hua (Policy & Governance Review, 2025)
Studies on regional collaborative governance based on China's institutional context are abundant, but the leadership perspective behind regional collaborative governance has rarely been discussed in previous studies. Based on a review of relational leadership theory, this study adopts the grounded theory methodology to study the three cities bordering Guangdong, Hunan, and Guangxi provinces, condensing the components of relational leadership in regional collaborative governance and the general explanatory framework. The research found that relational leadership in regional collaborative governance is composed of mission-driven, social capital, governance resources, trust shaping, common learning, interaction mechanisms, and public value. Among them, mission-driven is the motivation, social capital and governance resources are the basic conditions, trust shaping and common learning are actions, the interaction mechanism is the carrier, and public value creation is the goal. At present, the main problem of regional collaborative governance is that the governance mechanism is "built but not run." It is necessary to build an effective network governance system through the relational leadership of leaders, improve the overall public leadership of regional governance, and promote a governance system to operate more effectively. This research not only explores the dynamic leadership process of regional collaborative governance, but also enriches the micro perspective of regional collaborative governance research, expands the theoretical space of collaborative leadership, makes up the "leadership deficit" in the field of regional collaborative governance, and has reference significance and practical enlightenment for further promoting the performance of collaborative governance in the cross-region context.